2021
DOI: 10.3390/jcm10020316
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Teeth Bleaching after Regenerative Endodontic Treatment: A Systematic Review

Abstract: The aim of this review is to evaluate of effectiveness of bleaching procedures used to treat discolored teeth subsequent to regenerative endodontic procedures (REPs) based on the review of in vitro and in vivo studies. This literature review was carried out according to the PRISMA guidelines. Four databases (PubMed, Scopus, the Cochrane Library, and Web of Science databases) were searched electronically, until 30 January 2020 without a year limit. The quality of studies was assessed using a modified methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Regenerative endodontics studies the potential for the regeneration of damaged pulp as well as the creation and delivery of replacement pulp-dentin tissues, and belongs in category of stem cell induction therapies. A blood clot formed inside the canal could affect the colour of the teeth [54,55]. The use of platelet-rich concentrates and transplanting stem cells into the tooth cavity can also have a significant impact on tooth discoloration, but this requires confirmation by research.…”
Section: Discussionmentioning
confidence: 99%
“…Regenerative endodontics studies the potential for the regeneration of damaged pulp as well as the creation and delivery of replacement pulp-dentin tissues, and belongs in category of stem cell induction therapies. A blood clot formed inside the canal could affect the colour of the teeth [54,55]. The use of platelet-rich concentrates and transplanting stem cells into the tooth cavity can also have a significant impact on tooth discoloration, but this requires confirmation by research.…”
Section: Discussionmentioning
confidence: 99%
“…Yasa et al reported that 35% hydrogen peroxide is more effective than sodium perborate in the whitening of teeth discolored by antibiotic pastes 26 . A recent systematic review 27 was not able to make a suitable conclusion because further studies are required for the creation of precise guidelines that would define the appropriate bleaching technique, material, and duration in discolored teeth after REPs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] One of the methods used to whiten the teeth is bleaching. [ 2 ] The study showed that antioxidants play a role in the effect of tooth bond strength caused by bleaching method those can produce free radicals that are left in the tooth structure; therefore, antioxidants are needed as free radical scavengers to increase the strength of dental restoration materials bonding to the substrate. [ 3 ] An antioxidant is a substrate or molecule that can inhibit free radical reactions and is available in synthetic or natural forms since natural antioxidant is hardly safer than a synthetic antioxidant.…”
Section: Introductionmentioning
confidence: 99%